2015
DOI: 10.1016/j.phrs.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARβ/δ protects cardiac myocytes from oxidative stress-induced apoptosis by suppressing generation of reactive oxygen/nitrogen species and expression of matrix metalloproteinases

Abstract: Heart failure still remains one of the leading causes of morbidity and mortality worldwide. A major contributing factor is reactive oxygen/nitrogen species (RONS) overproduction which is associated with cardiac remodeling partly through cardiomyocyte apoptosis. Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that belong to the nuclear receptor superfamily and have been implicated in cardioprotection. However, the molecular mechanisms are largely unexplored. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Selective PPARβ/δ agonists have also been shown to have beneficial cytoprotective effects in rat cardiomyocytes subjected to oxidative stress (Barlaka, et al, 2015). To date there are no clinical trials that have studied PPARα agonists as specific metabolic therapies in HF.…”
Section: Increased Fatty Acid Utilizationmentioning
confidence: 99%
“…Selective PPARβ/δ agonists have also been shown to have beneficial cytoprotective effects in rat cardiomyocytes subjected to oxidative stress (Barlaka, et al, 2015). To date there are no clinical trials that have studied PPARα agonists as specific metabolic therapies in HF.…”
Section: Increased Fatty Acid Utilizationmentioning
confidence: 99%
“…PPAR regulate the expression of genes that are mostly involved in lipid and carbohydrate metabolism, energy production, and anti-inflammation activities [11]. Barlaka et al [12] reported that a novel connection between PPAR signaling and downregulation of matrix metalloproteinases (MMP) in cardiac myocytes may be involved in the management of oxidative stress-induced cardiac dysfunction. Our recent study demonstrated that Aloe sterol significantly prevented an increase in the total protein expression of MMP-2 (active and pro) and MMP-9 (active and pro) in ultraviolet B (UVB)-irradiated mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of Bcl-2 family proteins (Bcl-2 and Bax) and attenuation of PPAR and caspase-3 cleavage were shown in adult cardiac myocytes pretreated with PPARb/d stress [104]. In the same study, transcriptional control of matrix metalloproteases (MMPs) resulting in the inhibition of apoptosis was also suggested.…”
Section: Ppars In the Regulation Of Cardiac Cell Deathmentioning
confidence: 74%
“…Specifically, cardiomyocytes-restricted PPARb/d deletion resulted in increased oxidative stress in the heart, mediated from Cu/Zn-SOD and Mn-SOD downregulation [102], while cardiomyocyte-restricted overexpression of a constitutively active PPARb/d enhanced antioxidant capacity resulting in improved cardiac performance under left ventricular pressure overload [103]. A recent in vitro study demonstrated suppression of ROS generation and oxidative stress in cultured cardiac myocytes treated with a PPARb/d agonist, implicating catalase upregulation [104]. Furthermore, PPARb/d has been suggested to inhibit ROS generation through the inhibition of NADPH oxidases in vascular smooth muscle cells exposed to angiotensin II [105].…”
Section: Ppars and Redox Balancementioning
confidence: 99%